Structure of Drosophilidae Assemblage (Insecta, Diptera) in Pampa Biome (São Luiz Gonzaga, RS) - Poppe, Jean Lucas; Valente, Vera Lúcia da Silva; Schmitz, Hermes José (Papéis Avulsos de Zoologia, 2012)
The Brazilian Pampa (the southernmost end of the country) is currently a highly modified environment because of increasing agricultural activities. In many places, only small parts of grasslands remain inside an agricultural landscape. Drosophilidae (Diptera) have been widely used as a potential bioindicators to monitor the effects of anthropogenic changes in natural environments. However, the fauna of Drosophilidae in the Pampa Biome from natural and disturbed environments, still remains largely unknown. The present study represents one of the first attempts to fill this gap, showing results from monthly collections in the municipality of São Luiz Gonzaga (28º24'28"S, 54º57'39"W), in the Brazilian Pampa. A species inventory was carried out in two contrasting environments, an urban zone and a forest remnant (rural zone). In both areas banana-baited traps were used to capture adult drosophilids. The identification was made using external morphology and male terminalia. In total, 13,379 drosophilids were analyzed (rural zone: N = 8,812 and Sobs = 25; urban zone: N = 4,567 and Sobs = 16). In the present study, 16 (60%) out of 26 species were found exclusively or preferentially in the forest. The period of highest richness was between the months of June to November (roughly winter and spring), and the period of lowest richness was from December to May (roughly summer and autumn). An analysis of cluster by the Coefficient of Jaccard showed that species composition slightly changes when the period of the year with higher temperatures (from January to May) is compared with the period with lower temperatures (from June to October). The species abundances were also highly affected by seasonality, as revealed by the Morisita Index, since the samples clustered into similar groups in consecutive periods and in the same season, showing the seasonal preference of some species. The time component was a determinant in the diversity of the assemblage, surpassing the spatial effect. The strong reduction in diversity in the urban area when compared to a small forest patch is evidence of the importance of the natural environments in maintaining the diversity in the Pampa biome, currently a highly disturbed landscape.